Effectiveness of Nutrition and Physical Activity Intervention Adherence in Diabetes Management: A Systematic Review - Dwight Mahaputera Marulitua Hutapea (PT. Anagata Sembagi Education, 2025)
Type 2 diabetes has developed into a global epidemic with a significant increase in prevalence, both in the world and in Indonesia. This disease not only impacts quality of life, but also places a large economic burden on the health care system. Although most diabetes interventions still focus on pharmacological treatment, non-pharmacological approaches such as nutritional interventions and increased physical activity have been shown to be effective in lowering blood glucose levels, increasing insulin sensitivity, and improving patients' metabolic profiles. However, the effectiveness of these interventions is highly dependent on patient compliance. Compliance with these interventions is influenced by psychological, socioeconomic, and health literacy factors. Intrinsic motivation and positive perceptions of the disease can increase patient commitment, while stress, depression, and limited access to healthy food and sports facilities can hinder compliance. High health literacy affects patients' understanding of treatment and their readiness to make behavioral changes. Approaches based on education, social support, and the use of digital technology can strengthen diabetes management and improve patient compliance. Therefore, effective interventions require a more personalized, interdisciplinary approach that is oriented towards long-term behavioral change to achieve sustainable results.